Light responsive liquid crystal soft matters: structures, properties, and applications. Issue 2 (3rd April 2019) - Kim, Dae-Yoon; Jeong, Kwang-Un
ABSTRACT: Stimuli-responsive soft matters have been recognised by many scientists and engineers as very important because of their inherent characteristics in response to environmental changes. In particular, there has been much progress over the last few years on light-responsive soft matters that can respond remotely. By controlling the packing behaviours and the physical properties of the photoresponsive liquid crystal (LC) molecules, the application field is expanding, including the use in flexible polarisers, patterned objects, logic devices, biomimetic photonic crystals and energy harvesting materials. This review discusses the general concept of azobenzene-based LC compounds from small molecules to macromolecules and their corresponding structural evolutions in solid states. Finally, we identify the challenges faced in the research of photoresponsive organic materials and present future applications.